Analisis Kemampuan Spasial Subjek Kelas X pada Materi Geometri - Putri Arbain; Budi Irwansyah; Srimuliati Srimuliati (LSM Catimore dan Sahabat Jl. Paya Ilang/Pertamina Desa Lemah Burbana, Takengon, Aceh Tengah 24552, 2026)
Spatial ability is an important aspect of human intelligence related to the skills of understanding, manipulating, and remembering the relationships between objects in space. This study aims to analyze the spatial abilities of 10th-grade students at SMK Negeri 1 Langsa in solving geometry problems. This study employed a descriptive qualitative approach with a sample of 20 10th-grade accounting students at SMK Negeri 1 Langsa during the odd semester of the 2025/2026 academic year. Subsequently, 3 students were selected for further analysis. The data collection techniques used included spatial ability tests, and interviews. The results showed that students’ spatial abilities fell into varying categories: high, moderate, and low. When examined by individual indicators, spatial perception achieved the highest scores, while mental rotation had the lowest scores. This indicates that students tend to be able to recognize three-dimensional shapes but still struggle to mentally visualize and manipulate the rotation of these shapes when solving geometry problems. The results of data triangulation showed consistency between the test results and the interviews, thereby strengthening the validity of the research data. Thus, it can be concluded that students’ spatial abilities in solving geometry problems have not yet developed optimally across all indicators, particularly in the aspect of mental rotation.